2015
DOI: 10.1007/s10339-015-0737-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically ordered tapping interferes more with one-digit addition than two-digit addition: a dual-task fMRI study

Abstract: Fingers are used as canonical representations for numbers across cultures. In previous imaging studies, it was shown that arithmetic processing activates neural resources that are known to participate in finger movements. Additionally, in one dual-task study, it was shown that anatomically ordered finger tapping disrupts addition and subtraction more than multiplication, possibly due to a long-lasting effect of early finger counting experiences on the neural correlates and organization of addition and subtract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Embodied accounts of mathematics, especially sensorimotor simulation theories (Soylu, 2011(Soylu, , 2016Svensson, 2007), address this missing component. The embodied account is corroborated by neurocognitive studies showing that the finger sensorimotor network continues to play a role in adults' number processing (Andres, Davare, Pesenti, Olivier, & Seron, 2004;Badets, Andres, Di Luca, & Pesenti, 2007;Di Luca & Pesenti, 2008;Rusconi, Walsh, & Butterworth, 2005;Soylu & Newman, 2016), and that early finger counting experiences leave a lasting effect on adults' performance and neural correlates for number processing (Newman & Soylu, 2014;Tschentscher, Hauk, Fischer, & Pulvermuller, 2012). The grounded model argues that number processing does not become disembodied with age and instead early bodily interactions help establish the number network and leave a lasting trace on numerical cognition.…”
Section: Embodied Approachesmentioning
confidence: 81%
See 1 more Smart Citation
“…Embodied accounts of mathematics, especially sensorimotor simulation theories (Soylu, 2011(Soylu, , 2016Svensson, 2007), address this missing component. The embodied account is corroborated by neurocognitive studies showing that the finger sensorimotor network continues to play a role in adults' number processing (Andres, Davare, Pesenti, Olivier, & Seron, 2004;Badets, Andres, Di Luca, & Pesenti, 2007;Di Luca & Pesenti, 2008;Rusconi, Walsh, & Butterworth, 2005;Soylu & Newman, 2016), and that early finger counting experiences leave a lasting effect on adults' performance and neural correlates for number processing (Newman & Soylu, 2014;Tschentscher, Hauk, Fischer, & Pulvermuller, 2012). The grounded model argues that number processing does not become disembodied with age and instead early bodily interactions help establish the number network and leave a lasting trace on numerical cognition.…”
Section: Embodied Approachesmentioning
confidence: 81%
“…They proposed that the finger counting-based strategies used in childhood for addition and subtraction, but not for multiplication, leads to an early grounding of addition and subtraction processes in finger representations. Soylu and Newman (2016) followed up on these findings and studied the interaction between arithmetic difficulty and tapping complexity in a dual-task fMRI study. They reported differential interference of finger movements on single-digit addition, compared to double-digit addition, and traced this effect to the modulation of activity in the left angular gyrus.…”
Section: The Relation Between Finger and Number Representations In Thmentioning
confidence: 99%
“…In the above discussed Berteletti and Booth (2015) study subtraction differentially activated motor cortex suggesting involvement of implicit finger counting strategies for subtraction but not multiplication. Also, Soylu and Newman (2016) explored the relation between addition and finger tapping, and found that one-digit addition is more affected from concurrent anatomically-ordered tapping than two-digit addition, which supports a specific association between addition fact retrieval and anatomically ordered finger movements in adults, possibly due to use of finger counting strategies that deploy anatomically ordered finger movements early in the development. This variance in the involvement of fingers may be related to the differences in the processing required for different arithmetic operations.…”
mentioning
confidence: 73%
“…Therefore, the differential correlation in the IPL may be due to differences in the way addition facts are stored in memory. Multiple studies with adult participants provide evidence for simple arithmetic, which is assumed to rely on retrieval, using finger-based representations (Andres et al, 2012;Michaux et al, 2013;Soylu & Newman, 2016), reminiscent of fingercounting strategies in early childhood. This phenomenon can be considered within the wider framework of embodied memory, where memory retrieval is considered to use mental simulation of the sensorimotor states involved in the construction of the memory (Glenberg, 1997).…”
Section: Differential Correlation In the Left Inferior Parietal Lobulementioning
confidence: 99%
“…Evidence for the existence of two motor control regimes for repetitive movements, an automatic and a cognitively controlled regime according to (i), where only the cognitive control mode shows interference under MCDT conditions according to (ii) comes from a study by Soylu and Newman (2016) . They observed underadditive effects in brain activation in an fMRI study where subjects had to perform finger-tapping movements under ST and MCDT conditions (calculation).…”
Section: Introductionmentioning
confidence: 99%